(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: (1) To evaluate the current status and feasibility of early mobilization in mechanically ventilated patients following neurosurgery; (2) To identify factors associated with early mobilization in this patient population. Subjects and methods: A cross-sectional study was conducted on 254 mechanically ventilated post-neurosurgical patients at the Anesthesiology and Resuscitation Center, Bach Mai Hospital from February to June 2025. Data were collected using a questionnaire, the Perme Score, and the ICU Mobility Scale (IMS). Results: The mean Perme Score improved significantly from 11.69 ± 4.9 at ICU admission to 18.4 ± 6.4 at ICU discharge (p < 0.001). The rate of early mobilization was 98.8%, with breathing exercises achieving good level (70.1%), limb exercises (59.8%), and walking exercises (30.3%). Factors associated with a higher risk of no improvement in mobility included: age ≥ 60 (OR = 3.65; p = 0.002), RASS < -2 (OR = 2.84; p = 0.01), Glasgow score ≤ 8 (OR = 2.5; p = 0.03), unstable hemodynamics (OR = 3.2; p = 0.005), and presence of comorbidities (OR = 4.7; p = 0.02). Conclusion: Early mobilization in mechanically ventilated patients after neurosurgery is implemented at a high rate and yields significant improvement. Risk factors should be carefully managed to optimize recovery outcomes.